Sizing and Performance Analysis of Hydrogen- and Battery-Based Powertrains, Integrated into a Passenger Train for a Regional Track, Located in Calabria (Italy) - Petronilla Fragiacomo; Francesco Piraino; Matteo Genovese; Lorenzo Flaccomio Nardi Dei; Daria Donati; Michele Vincenzo Migliarese Caputi; Domenico Borello (Energies, 2022)
In order to decarbonize the rail industry, the development of innovative locomotives with the ability to use multiple energy sources, constituting hybrid powertrains, plays a central role in transitioning from conventional diesel trains. In this paper, four configurations based on suitable combinations of fuel cells and/or batteries are designed to replace or supplement a diesel/overhead line powertrain on a real passenger train (the Hitachi Blues) tested on an existing regional track, the Catanzaro Lido–Reggio Calabria line (Italy), managed by Trenitalia SpA. (Italy). The configurations (namely battery–electrified line, full-battery, fuel cell–battery–electrified line, and fuel cell–battery) are first sized with the intention of completing a round trip, then integrated on board with diesel engine replacement in mind, and finally occupy a portion of the passenger area within two locomotives. The achieved performance is thoroughly examined in terms of fuel cell efficiency (greater than 47%), hydrogen consumption (less than 72 kg), braking energy recovery (approximately 300 kWh), and battery interval SOC.